KUALITAS UDARA DALAM RUANG DI DAERAH PARKIR BASEMENT DAN PARKIR UPPERGROUND (STUDI KASUS DI SUPERMARKET SEMARANG) - Huboyo, Haryono Setiyo; Istirokhatun, Titik; Sutrisno, Endro (Universitas Diponegoro, 2016)
Ever increasing building growth in urban areas is limited by land availability. Lack of space in this area lead to build high rise building rather landed building. In this type of building, parking area is built in the basement and or upperground inside the building. Within this enclosed space, indoor air quality might a problem. This study focus to compare emerged pollutants between basement parking area and upperground parking area in supermarket building. The dust sampler, the impinger and the CO monitor were used to measure TSP, NO 2 and CO concentrations respectively in these areas during supermarket operations. In the basement area, in particular, the TSP concentrations tend to exceeds 300 µg/m 3 mainly at weekend period. While for NO 2 and CO concentrations still meet the air quality standard. Based on these findings it seems the main source of pollutants was derived from dust resuspension. Thus, the mitigation measures to reduce this dust resuspension should be emphasized in order to prevent air quality deterioration in the basement parking area.